(untitled) (Scottish Historical and Archaeological Internet Reports, 2008)
A brief account of methodology is followed by an archaeological description which is organised into four phases: phase 1 is 8th-9th centuries; phase 2 is 9th-10th centuries; phase 3 is 10th-11th centuries; phase 4 is 15th century. This is followed by a brief account of the radiocarbon dating. There are specialist reports on pottery, geochemical fingerprinting of pottery, copper alloy and bone objects, metallurgical waste analysis, faunal remains and plant remains.